2018
DOI: 10.33225/jbse/18.17.162
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Educational Efficiency and Students’ Involvement in the Flipped Biology Classroom in Primary School

Abstract: The Flipped Classroom (FC) is a teaching approach in which students gain the first-exposure learning with online materials outside the classroom, and then, in the classroom, they focus on interactive or engaging exercises. Despite its considerable publicity, the studies focused on the FC in primary education are deficient. The aim of this research is to determine efficiency and students’ involvement in the flipped Biology classroom in primary school, compared to the conventional classroom (CC) approach. Educat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 62 publications
(70 reference statements)
2
12
0
Order By: Relevance
“…As it reflects an individual's invested cognitive capacity, subjective measurement of mental effort can be applied. Paas and associates (Paas et al, 2003) claim that subjective measures have proven to be valid and reliable and many of the studies so far have relied on the subjects' selfreport on the invested mental effort upon the completion of a task (e.g., Milenković et al, 2014;Radulović et al, 2016;Županec et al, 2018). In addition, this dimension, together with students' achievement, has been widely used by education researchers for determining the instructional efficiency of a teaching approach (Van Gog & Paas, 2008).…”
Section: Flipped Classroom Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…As it reflects an individual's invested cognitive capacity, subjective measurement of mental effort can be applied. Paas and associates (Paas et al, 2003) claim that subjective measures have proven to be valid and reliable and many of the studies so far have relied on the subjects' selfreport on the invested mental effort upon the completion of a task (e.g., Milenković et al, 2014;Radulović et al, 2016;Županec et al, 2018). In addition, this dimension, together with students' achievement, has been widely used by education researchers for determining the instructional efficiency of a teaching approach (Van Gog & Paas, 2008).…”
Section: Flipped Classroom Approachmentioning
confidence: 99%
“…The measure, therefore, is used in the present study for assessing the implementation of the FC in relation to the conventional approach in teaching and learning academic vocabulary. Additional reason for including this dimension in the study is the fact that there are some reports (Mattis, 2015;Županec et al, 2018) of students investing less mental effort in solving tasks when taught in the flipped environment. None of these reports, to the best of the authors' knowledge, fall within the scope of L2 learning.…”
Section: Flipped Classroom Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…This model is said to be flipped because what used to be done at school / college is now done at home and vice versa [9]. The number of research studies examining the impact of flipped classroom on student performance in Biology education has increased in recent years [13][14][15][16][17][18][19]. Although all the above researchers researched points out the FC as a good alternative to traditional classroom, there are also those studies that showed that traditional teaching was more efficient in terms of student performance (at the level of knowledge and application) compared to FC [20].…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers have found that digital technology positively impacts student performance [9][10], pointing out that learning material presented through words and images is easier for students. However, some researchers [11] argue that multiple representations, especially in that case, do not help to form mental schemes in learning.…”
Section: Introductionmentioning
confidence: 99%